A clinical study on social stigma and trends of contraception at a tertiary care centre - Agarwal, Shubhra; Najam, Rehana; Agarwal, Arjit (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: The most important problem with developing countries like India are facing today is uncontrolled growth of population. The extent of acceptance of the Family Planning methods still varies within societies and also among different castes and religious groups. The objective of the study was to determine the prevalence of different types of contraceptive usage among eligible couples (aged 15-45 years) and to study different variables affecting the prevalence of contraceptive use among eligible couples. Methods: A cross Sectional study by interview method of Eligible couples from august 2015 to January 2016 at TMMC and RC Moradabad was done. Results: Contraceptive prevalence was found to be 27.08%. Among the permanent sterilization methods, the most commonly used method was Tubectomy (21.5%). Among the spacing methods Condoms, Oral Contraceptive Pills and Intra-Uterine Devices were used by 12%, 13% and 13% of the eligible couples respectively. Conclusions: Total CPR in our study population was found to be 27.08% as compared to 40.4% of India which suggests a lot of motivation and education is further required. In the long-term, education of the girl child and male involvement in family planning will empower women to take decisions about their reproductive health.